Deaf signers in Flanders and 25 years of Community Interpreting - Van Herreweghe, Mieke; Vermeerbergen, Myriam (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Looking back on 25 years of Community Interpreting in the Deaf communi - ty in Flanders at least three issues seem to be noteworthy.Linguistic research into Flemish Sign Language has clearly influenced the sign language interpreter trainingprogrammes. When thefirst programmes were started up in the early 1980s, interpreter students were taught Signed Dutch. The shift to Flemish Sign Language came about in the latter half of the 1990s, some years after the first results of Flemish Sign Language research were made available in the public domain.A second important factor is the professionalisation of the interpreter. The internationally recognised evolution from a ‘helper philosophy’ via a ‘machine (conduit) philosophy’ to a ‘bilingual-bicultural philosophy’ has also taken place in Flanders.Thirdly, we can see a certain impact of Community Interpreting on Deaf Empowerment. Since it is very hard to exactly identify this and more research would be necessary, these will only be briefand tentative statements.